Relação entre os diferentes níveis de capital social individual e comunitário com a qualidade de vida relacionada à saúde bucal de adolescentes - Silva, Paola Mello da (2024)
Social capital (SC) is known as the social networks in which individuals are inserted, as well as the social ties they create with their peers and their coexistence with these people. Oral health-related quality of life (OHRQoL) is a multidimensional construct that considers how oral health conditions affect the well-being of individuals and their daily activities such as eating, sleeping, their social interactions and self-esteem. There is a significant amount of evidence that points to the relationship among social capital and health, especially OHRQoL. However, little is known about how much this effect is caused by community or individual social capital, and whether one stands out in relation to the other. Therefore, the aim of this study was to evaluate the relationship between different levels of SC and the OHRQoL of adolescents. The hypothesis of this study is that the presence of some level of SC, whether individual or community, has a positive relationship with the OHRQoL of adolescents. For this purpose, a cross-sectional study nested in a cohort study with 10 years of follow-up was carried out. The cohort began in 2010 in the Childish National Vaccination Day evaluating 639 children were 1 to 5 years old, and had assessments in 2012, 2017, and 2020. This study used data only from the last follow-up, where 429 adolescents were 11 to 15 years old was founded in their houses or in the schools. The OHRQoL assessment was done using the reduced version of the CPQ11-14 questionnaire. The community social capital was evaluated by the neighborhood social support networks (community groups present, community cultural centers and residents’ association); the individual social capital was evaluated by the religious activity frequency, volunteer work participation and confidence with friends and neighbor. Furthermore, was evaluated clinical, socioeconomics and psychosocial variables, and behavior aspects as possible confounders. The relationship among the different levels of SC and OHRQoL of adolescents was assessed using adjusted Poisson regression analysis. For this, an interaction variable was created considering the levels of social capital, considering multiplicative scales. The results showed that adolescents with low community SC and low individual SC had higher scores on the CPQ11-14, indicating worse OHRQoL. The relationship among high and low levels of social capital was not associated with CPQ11-14 scores, indicating that no level stands out over the other. Thus, it can be concluded that only the total lack of social capital (both low individual and community levels) significantly affected the OHRQoL of adolescents, indicating that the presence of some level of social capital, whether individual or community, is already sufficient to improve the OHRQoL scores of adolescents.